2019
DOI: 10.1101/515023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and Safety of Immunosuppressive Treatment in IgA Nephropathy: A Meta-analysis of Randomized Controlled Trials

Abstract: 25 Background: There is some controversy regarding the efficacy and safety of 26 immunosuppressive agents for the treatment of kidney diseases. The recent STOP-IgAN and 27 TESTING studies have focused attention on the application of immunosuppressive agents in 28 IgA nephropathy (IgAN). This study investigated the benefits and risks of 29 immunosuppressive agents in IgAN.30 Methods: MEDLINE, EMBASE, the Cochrane Library, and article reference lists were 31 searched for randomized controlled trials (RCTs) compa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…1 Since then, the beneficial effects of treatment strategies for the prevention of progression to end-stage renal disease (ESRD) have been reported. [2][3][4][5][6] Indications for these therapies are generally decided based on disease activity, such as proteinuria and haematuria levels, renal function, and the patient's background, including age, presence of hypertension, and comorbidities. [7][8][9] Histological findings should also be considered, and several validation and classification systems that predict the renal prognosis have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…1 Since then, the beneficial effects of treatment strategies for the prevention of progression to end-stage renal disease (ESRD) have been reported. [2][3][4][5][6] Indications for these therapies are generally decided based on disease activity, such as proteinuria and haematuria levels, renal function, and the patient's background, including age, presence of hypertension, and comorbidities. [7][8][9] Histological findings should also be considered, and several validation and classification systems that predict the renal prognosis have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our results also showed that the 2 treatment regimens had a similar risk of adverse events, which was different from the results of other studies. The metaanalyses using non-immunosuppressants/corticosteroids as a reference showed that immunosuppressants/ corticosteroids significantly increased the incidence of adverse events (30,31). The possible reason may be that our reference objects were patients receiving a single supportive treatment, and the types of adverse events in this study were diverse and mainly mild with good tolerance, including diarrhea, gastrointestinal discomfort, cough, insomnia, nausea, and mild hair loss.…”
Section: Discussionmentioning
confidence: 91%
“…Initially, the malady was believed to be the uncommon and benign cause of rehashed hematuria. Be that as it may, it has since gotten to be clear that IgAN is neither rare nor benign [1] and is the frequent cause of primary glomerulonephritis around the world [1,2]. IgAN in up to 15-20% of patients within 10 years from the malady onset which leads to end-stage renal disease (ESRD) and 30-40% within 20 years [2].…”
Section: Introductionmentioning
confidence: 99%